New species and records of Scolytodes (Coleoptera, Curculionidae: Scolytinae) from South America - Jordal, Bjarte H. (Zootaxa, 2013)
Seventeen new species of Scolytodes Ferrari are described from Venezuela, Ecuador, Peru, Bolivia and Argentina: Scolytodes cenchros, S. concavifrons, S. conpunctus, S. fraterniatratus, S. frontocarinatus, S. solarius and S. trigonus from Cecropia leafstalks; S. pascopomus from a fruit husk; S. obovatus, S. clusiaphilus, S. clusiapraelatus and S. uniseriatus from Clusia litter sifting; S. grossepunctatus and S. fulvus from general litter sifting; and S. inusitatus, S. sagittarius and S. sus collected by flight intercept traps. The synonymy of S. imitans and S. nitidissimus is confirmed. Additional South American records are given for S. chapuisi (Ecuador), S. interpunctatus (Peru), S. maurus (Ecuador), and S. suspectus (Ecuador), all taken from Cecropia leafstalks, and S. similis (Peru) and S. unipunctatus (Bolivia).